Understanding the Aspired Attributes of Luxury Product for Millennials - B. Wibawa, Pramis; Wibawa, Basuki (International Journal of Engineering and Technology, 2019)
Despite the concept of millennial has been a growing research object and interest; the lack of a clear conception of their buying behaviour on luxury products is still evident. Luxury has different meanings at different time, in different culture and amongst different demographics.Â This thesis aims to classify what are the most appealing attributes and/ or characteristics of luxury brands and how consumers, particularly millennials, determine it.to gain crucial insights form the subject under investigation, this work introduces the concept of millennial generation cohort before discussing the buying behaviors of this cohort, as well as unique traits with which this customer segment continues to be associated. The discussion culminates into an examination of the concept of luxury and how millennials interact with luxury brands, as well as their motivation for preferring these brands. In turn, the results obtained form the primary research are presented in a quest to establish possible parallels with findings documented in the current literature. Finally, this paper offers a conclusion, some of the study limitations, and recommendations regarding future research. Â Â Â